To solve the system of equations using substitution, we can solve one equation for one variable and substitute it into the other equation.
Let's solve the second equation for x:
x = -3y - 7
Now, substitute this value of x into the first equation:
6y + 5(-3y - 7) = 8
Simplifying the equation:
6y - 15y - 35 = 8
-9y - 35 = 8
-9y = 43
y = 43/(-9)
y = -43/9
Now substitute this value of y into the second equation to find x:
x + 3(-43/9) = -7
x - 129/9 = -7
x - 43/3 = -7
x = -7 + 43/3
x = -21/3 + 43/3
x = 22/3
So the solution to the original system of equations is (x, y) = (22/3, -43/9).
Now we can graph the original equations on Desmos to determine if this solution is also a solution to the new equation.
Note: Determine whether the solution to the new equation is a solution to the old system of equations by graphing. Use Desmos!
(1 point)
The solution to the original system of equations a solution to the new equation..
Solve the system of equations (is also or is not) by SUBSTITUTION
6y + 5x = 8
x + 3y = - 7
1 answer